Synthesis of chiral polymorph A-enriched zeolite Beta with an extremely concentrated fluoride route - Tong, Mingquan (Sci Rep, 2015)
Chiral zeolitic materials with intrinsically chiral frameworks are highly desired because they can combine both shape selectivity and enantioselectivity. In the field of zeolite, the synthesis of chiral polymorph A of zeolite Beta or chiral polymorph A-enriched zeolite Beta is one of the biggest challenges. We demonstrate here a generalized extremely concentrated fluoride route for the synthesis of chiral polymorph A-enriched zeolite Beta in the presence of five achiral organic structure-directing agents. The polymorph A-enriched Ti-Beta shows a higher enantioselectivity for the asymmetric epoxidation of alkenes than the normal Ti-Beta.